THE MEDIATING ROLE OF SELF-EFFICACY IN TRAINING TRANSFER: A SYSTEMATIC REVIEW - Norlela Samad; Mohd Faiq Abd Aziz; Suriani Ismail; Abdul Rashid Shoib (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
The mediating role of self-efficacy in training transfer remains a critical yet underexplored area within training and development research. This systematic literature review (SLR) seeks to synthesise current evidence on how self-efficacy influences the application of newly acquired skills in diverse contexts. Addressing the gap in cohesive understanding, the review applied the PRISMA protocol to guide a systematic search across two databases, Scopus and Web of Science, resulting in the selection of 33 primary studies. The findings were categorised into three themes: (1) Self-Efficacy and Motivation Factors in Training Transfer, (2) Training Transfer in Educational and Academic Settings, and (3) Organisational, Leadership, and Workplace Factors in Training Transfer. Studies within the first theme emphasised the strong interplay between self-efficacy and motivation to transfer, directly impacting transfer success. The second theme revealed that self-efficacy enhances the transition of knowledge from training to practical application in academic and clinical training. Meanwhile, the third theme demonstrated how workplace support structures, leadership behaviours, and organisational climates foster self-efficacy, leading to improved transfer outcomes. The review underscores that fostering self-efficacy throughout various phases of the training journey can play a crucial role in enhancing the extent to which acquired skills and knowledge are effectively applied in the workplace. These findings offer valuable theoretical and practical implications for training designers, educators, and organisational leaders aiming to optimise learning transfer in various professional settings.